Challenges in preserving the “good doctor” norm: physicians' discourses on changes to the medical logic during the initial wave of the COVID-19 pandemic - Härgestam, Maria; Jacobsson, Maritha; Bååthe, Fredrik; Brulin, Emma (Frontiers in Psychology, 2023)
The COVID-19 pandemic was a tremendous challenge to the practice of modern medicine. In this study, we use neo-institutional theory to gain an in-depth understanding of how physicians in Sweden narrate how they position themselves as physicians when practicing modern medicine during the first wave of the pandemic. At focus is the medical logic, which integrates rules and routines based on medical evidence, practical experience, and patient perspectives in clinical decision-making. To understand how physicians construct their versions of the pandemic and how it impacted the medical logic in which they practice, we analysed the interviews by discursive psychology. The interpretative repertoires, showed how COVID-19 created an experience of a knowledge vacuum in medical logic and how physicians dealt with clinical patient dilemmas. They had to find unorthodox ways to rebuild a sense of medical evidence while still being responsible for clinical decision-making for patients with critical care needs.